Financial policy and companies' sustainable growth - Naumoski, Aleksandar (My University, 2022)
This paper investigates the intercompany-specific characteristics as a determinant of the sustainable growth rate. We researched a sample of companies listed on the Macedonian stock exchanges. We found that the average actual growth rate for the 2010-2019 period is only 0.38%, while the sustainable growth rate was 1.42%. This is because of the poor operating performance of the companies, moderate leverage, and average retention ratio of 82.5% for the whole sample. The actual growth rate in specific years is drastically higher than the sustainable growth rate, while in certain years it is negative. The sustainable growth rate is positively affected by the profit margin, retention ratio, asset turnover, financial leverage, and ROE, and it is negatively affected by the operating cash flow, company size, growth opportunities, and non-debt tax shield.
Keywords: financial policy; sustainable growth rate; retention ratio; dividend payout; North Macedonia